Development and validation of Child-Friendly School Environment Questionnaire from Chinese culture - Xiao, Erping; Sun, Mengju; Lv, Kexin; Zhu, Xinyi; Jia, Wenbin (Frontiers in Psychology, 2023)
In the context of building Child-Friendly Cities in China, child-friendly school environments are considered as having a profound impact on children's development and growth. This study presents the development and validation of the Child-friendly School Environment Questionnaire for assessing a child-friendly school environment. Utilizing open-ended questions and interviews, an initial questionnaire on the child-friendly school environment was compiled. An exploratory factor analysis of the preliminary test results with 696 primary school children in grades three to six was conducted to refine the questionnaire into a formal 19-item questionnaire. Subsequently, a confirmatory factor analysis was performed to analyze the evaluation results of 807 primary school children in grades three to six. The results indicated that a child-friendly school environment is a multi-dimensional construct encompassing Environment Friendly, Teaching Friendly, Peer Friendly, and Children Participation, with good reliability and validity. The promising outcomes of this study suggest that the Child-Friendly School Environment Questionnaire can be widely used as a powerful evaluation tool for the child-friendly school education practice in the future.